Descriptive and Categorical Delimitation of the Theories of “Didactics” - Ioannis Fykaris; Maria Bimpa; Filippos Evangelou; Anna Georgiou; Ioanna Katerini; Dimitrios Papadimitriou; Ioanna Syriou; Vasileios Zagkotas (Journal of Studies in Education, 2024)
This literature review aims to describe the theoretical approaches to Didactics as they have emerged in modern literature and the classification of these theories to realize their dynamics in the teaching practice. Didactics, either as a macro-theory or a micro-theory and methodology of teaching, constitutes its theoretical background, thus significantly contributing to decisions made about the models, methods, and means employed in the instructional design. In this respect, it refers to the theory and practical applications which underlie instruction. Its wide range of definitions, which are based on different and often conflicting theoretical approaches, have sustained an ongoing reflection and debate on the epistemological entity of Didactics. The present study views Didactics as the framework for the scientific and theoretical documentation of teaching, which it perceives as a complex multifactorial phenomenon.